Antioxidant activity of Juglans regia L., Juglandaceae pericarp from Sumadija region - Kojičić, Ksenija Z; Tadić, Vanja; Sovrlić, Miroslav; Cupara, Snežana (PONS - medicinski časopis, 2018)
The pericarp (green husk) of walnut (Juglans regia L., Juglandaceae) cultivars growing in different regions has been tested for antioxidant activity. In our work we have investigated pericarp of unripe walnut fruit, originated from Sumadija region of Serbia. The extract was obtained by methanol. Antioxidant activity was evaluated by DPPH radical scavenging assay. Contents of phenols and tannins were determined. The antioxidant activity of walnut pericarp was concentration dependent and within the range 25,32-79,35 %. IC50 was 1,223 mg/ml. Content of phenols was 119,8mg GAE/g and tannins 2,645 %. Key words: Juglans regia L., pericarp, antioxidant activity, total phenols, tannins